2002
DOI: 10.1002/pola.10513
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition–fragmentation chain‐transfer graft polymerization of styrene: Solid phases for organic and peptide synthesis

Abstract: The γ‐initiated reversible addition–fragmentation chain‐transfer (RAFT)‐agent‐mediated free‐radical graft polymerization of styrene onto a polypropylene solid phase has been performed with cumyl phenyldithioacetate (CPDA). The initial CPDA concentrations range between 1 × 10−2 and 2 × 10−3 mol L−1 with dose rates of 0.18, 0.08, 0.07, 0.05, and 0.03 kGy h−1. The RAFT graft polymerization is compared with the conventional free‐radical graft polymerization of styrene onto polypropylene. Both processes show two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 46 publications
2
84
0
Order By: Relevance
“…[13][14][15] In a number of publications, the technique has proven to be useful for the preparation of polymer conjugated systems by in situ polymerization of monomers from the RAFT-agent-anchored substrates. [16][17][18][19][20][21] However, to our knowledge, the utility of the RAFT technique in the in situ preparation of polymerbiomacromolecule conjugates has not yet been reported. Herein, we demonstrate the first, RAFT-mediated in situ preparation of polymer-protein conjugates.…”
mentioning
confidence: 99%
“…[13][14][15] In a number of publications, the technique has proven to be useful for the preparation of polymer conjugated systems by in situ polymerization of monomers from the RAFT-agent-anchored substrates. [16][17][18][19][20][21] However, to our knowledge, the utility of the RAFT technique in the in situ preparation of polymerbiomacromolecule conjugates has not yet been reported. Herein, we demonstrate the first, RAFT-mediated in situ preparation of polymer-protein conjugates.…”
mentioning
confidence: 99%
“…In practice, the radiation doses required to achieve graft in the simultaneous method are lower than the other two methods. The reversible addition fragmentation transfer mechanism (discussed earlier) can also operate in the radiation initiated grafting technique [147,148] . In the ionic mode, two different types (cationic and anionic) mechanisms can operate.…”
Section: (I) Preirradiation Techniquesmentioning
confidence: 99%
“…More recently Bai et al found that controlled/living free radical polymerizations of vinyl monomers can be performed under 60 Co g-ray irradiation in the presence of dibenzyl trithiocarbonate [11][12][13] and dithiobenzoic acid, [14] though the g-ray irradiated polymerization is generally very difficult to control. Subsequently, Quinn et al reported the living free radical polymerizations of styrene [15] and methyl methacrylate, [16] and the graft polymerization of styrene onto a polypropylene solid phase [17,18] under g-ray irradiation with cumyl phenyldithioacetate and cumyl dithiobenzoate. Pan and co-workers [19] successfully prepared cyclic poly(methyl acrylate) with controlled ring size and narrow-ring-size distribution by the g-ray irradiation polymerization of methyl acrylate at À30 8C in the presence of cyclic initiator.…”
Section: Introductionmentioning
confidence: 99%